2011 IEEE International Ultrasonics Symposium 2011
DOI: 10.1109/ultsym.2011.0561
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic imaging using synthetic aperture sequential beamforming

Abstract: Abstract-The paper investigates Second Harmonic Imaging (SHI) using Synthetic Aperture Sequential Beamforming (SASB). The investigation is made by an experimental Synthetic Aperture Real-time Ultrasound System (SARUS). A linear array transducer is used to scan 4 wires at the image depths of {22.5, 47.5, 72.5, 97.5} mm, respectively. Three different experiments are made using three different transmit foci at 10 mm, 25 mm and 50 mm. A 2-cycle sine wave with a center frequency of 5 MHz is used as the excitation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…SASB can generate an acoustic field intense enough to create harmonics for THI, and it has been suggested that these techniques be combined to improve the image quality of SASB even further. The pulse inversion technique was used to generate THI, and the beamforming steps for the final SASB-THI image are illustrated in Figure 1 (Hemmsen et al 2014b;Rasmussen et al 2012;Yigang et al 2011). In a preliminary study in which healthy volunteers were scanned, two radiologists evaluated the image quality of SASB-THI as equal to that of a conventional imaging technique combined with THI (DRF-THI), indicating that SASB-THI can be used for medical imaging (Rasmussen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SASB can generate an acoustic field intense enough to create harmonics for THI, and it has been suggested that these techniques be combined to improve the image quality of SASB even further. The pulse inversion technique was used to generate THI, and the beamforming steps for the final SASB-THI image are illustrated in Figure 1 (Hemmsen et al 2014b;Rasmussen et al 2012;Yigang et al 2011). In a preliminary study in which healthy volunteers were scanned, two radiologists evaluated the image quality of SASB-THI as equal to that of a conventional imaging technique combined with THI (DRF-THI), indicating that SASB-THI can be used for medical imaging (Rasmussen et al 2013).…”
Section: Introductionmentioning
confidence: 99%